Designing a Multiple Submission Policy Supporting Mastery Learning for a Design Thinking Class in a Purely Online Learning Environment - Amurao, Marianne Kayle (Archīum Ateneo, 2021)
Mastery learning is defined as an approach where students are equipped with complex skills required in the VUCA world instead of simple skills that only apply to traditional classrooms. One way to encourage mastery learning in the classroom is through repeated assessment, specifically formative ones. In this paper, we describe our experience in designing a multiple submission policy to support mastery learning for a design thinking class taught purely online amidst lockdowns due to COVID. The transition to online learning and today’s context presented an opportunity to target mastery learning instead of traditional learning outcomes, which we achieved in two ways. First, we elevated the assessments’ level on Bloom’s taxonomy and encouraged iteration by providing feedback to guide metacognition. Second, we built creative confidence providing a safety net for graded assessments, which helped address fears of judgment and lack of control. In the process, we also overcame transactional distance to help promote self-efficacy, especially those with initially low grades. The policy was implemented with the aid of technology, which served as the medium for learning and dialogue. The use of technology in this study allowed for practices that were otherwise not implemented or even considered in previous trials of the class. The study resulted in positive feedback and improved quality of submissions from participants.